How Do the Accrual Pattern and Follow‐Up Duration Affect the Hazard Ratio Estimate When the Proportional Hazards Assumption Is Violated?. (10th September 2018) - Horiguchi, Miki; Hassett, Michael J.; Uno, Hajime
Abstract : In randomized clinical trials, the magnitude of the treatment effect is often reported using the hazard ratio (HR) even when the proportional hazards (PH) assumption is not met. Conducting numerical studies, this commentary illustrates how/why the HR estimate via the standard Cox's procedure is difficult to interpret even as an "average" treatment effect for non‐PH cases.